Identificação de ortólogos e famílias gênicas em dez espécies de abelhas com diferentes comportamentos sociais - Melo, Sarah Calado Galvão de (Universidade Federal de São Carlos, 2025)
Gene sequences that share a common ancestry are known as homologous and can be classified into orthologs or paralogs. Paralogs originate from duplications of the ancestral gene in a given species and are responsible for the expansion of gene families, which are groups of genes that have similar functions. In contrast, orthologs arise from speciation events in which a gene of the common ancestry is maintained in the novel species. As they share a common origin, orthologs sequences from different species display high similarity. Therefore, frequently, the ortholog encoded proteins display conserved structure and function in different species. Thus, the identification of orthologs helps in the gene annotation of novel genomes and in the inference of the evolutionary relationship between species. In addition, the quantification and identification of gene family expansions can help us understand functional innovation in a genome, such as the eusociality of bees. Thus, this study aimed to identify create a database of orthologs for ten bee species with available genomes that differ in social behavior and to identify gene families, evaluating whether there was expansion or retraction in the studied species. For this purpose, the protein sequences of the species were aligned using DIAMOND and the Reciprocal Best Hit (RBH) approach was used to identify the best ortholog candidates, totaling 45 pairwise combinations between the 10 species. In parallel, the OrthoFinder tool was used to identify orthologs and paralogs between species. The RBH approach identified 4.979 1:1 orthologs and the OrthoFinder 5.755, with 4.347 genes identified as 1:1 orthologs by both approachesThe evaluation of gene families using the CAFE tool identified 200 unique expansions for at least one of the eusocial bee species, 83 in the simple social bees and only 6 in the solitary bees. In addition to identifying orthologs among the ten bee species, this work contributed to the creation of an automated analysis flow that can be modified to analyze genomic data from other species.
Identification of orthologs and gene families in ten bee species with different social behaviors
Keywords: Bioinformática; Homologia de sequências; Famílias gênicas; Evolução molecular; Abelha; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS::GENETICA